Uma arqueogenealogia do projeto Leia Mulheres: leitura, resist?ncia e produ??o de subjetividades - Amorim, Mayane Santos (2024)
The general aim of this thesis is to investigate the way in which the Leia Mulheres project is constituted, with attention to the discourses on reading, women readers and woman authors, considering their conditions of emergence/resistance and their modalities of knowledge (archaeological practices) and power (genealogical practices). To do this, we analyzed the discourses of and discourses about Leia Mulheres, i.e. the statements coming from the publications on the social networks of the Leia Mulheres Feira de Santana group and the Leia Mulheres website (central group), as well as statements about the Project, coming from its repercussions in other media and institutions of its social circulation, such as national newspapers and blogs, paying attention to the relations of knowledge/power that run through it. This study is anchored theoretically and methodologically in the perspective of Foucaultianos Discursive Studies, which is based on the archegenealogical method, which gives us the necessary support to discuss the relationships between subject, discourse, knowledge and power and the production of subjectivities, based on a sense of discourse as a historically constituted practice. We found that the practice of reading texts by women, within the scope of Leia Mulheres, represents an act of resistance, a practice of ethical freedom, given that, by its very nature as a discourse, it modifies the subjects' way of being, the way they experience themselves and how they relate to others.